The impacts of the COVID-19 pandemic on indirect costs of mental illness and behavioral disorders in Poland - Sobczyk, Karolina; Holecki, Tomasz; Rogalska, Anna (Frontiers in Public Health, 2023)
Introduction In various research, the estimation of the disease’s economic burden has been taken into consideration. But given the fact that different settings will have distinguished consequences, determining the economic burden of COVID-19 in the studied environment is of great importance. As a result, this study aimed to show the change in indirect costs of mental health problems due to the COVID-19 pandemic in Poland. Methods and Results Indirect costs related to mental health problems were analyzed from the perspective of the Social Insurance Institution in Poland. In 2021, they amounted to about 285.8 billion PLN (Polish currency) [61.1 billion EUR (European currency)], up 6% from the previous year. A large increase in spending on disability benefits was observed for 2019–2021 (+14.7%). Disease groups generating the highest expenditures in the structure of total expenditures on incapacity benefits in 2021 in Poland were mental health problems (16.7% of total expenditures). Expenditures on disability benefits related to mental health problems incurred by Social Security in 2021 amounted to about 7.42 billion PLN [1.6 billion EUR] and were 19.4% higher than in 2019 (before the pandemic). In the 2012–2019 period, there was a significant decrease in expenses related to inpatient rehabilitation (41.3%), while in 2020–2021, these expenses decreased several times as the epidemiological situation related to the COVID pandemic reduced access to such services. Discussion This is the first study on the economic burden of COVID-19 indirect costs in Poland. Calculating the economic impact is crucial, particularly when there is a large disease outbreak and countries are severely constrained by financial resources. Doing so could aid in the development of effective social security policies. As shown in this study, the indirect costs of absenteeism expenses due to mental health problems increased significantly during the COVID-19 pandemic. It is necessary to take all possible measures, both in the field of primary and secondary prevention, to prevent disability and exclusion from the labor market of people affected by mental health problems, which is justified by epidemiological data and financial data on the expenses incurred by Social Security for social insurance benefits.